Savage attack: tribal insurgency in India - Bates, Crispin; Shah, Alpa (Social Science Press, 2014)
Papers presented at a conference held at London in June 2008
Includes bibliographical references
Keywords: India -- Congresses -- Politics and government; India -- Politics and government -- 1919-1947 -- Congresses; India -- History -- British occupation, 1765-1947; Konferenzschrift -- 2008 -- London; Geschichte; Aufstand; Indigenes Volk; Indien